Prevalence and phenotype of eating disorders in assisted reproduction: a systematic review - Marine Le Floch; Anaïs Crohin; Philippe Duverger; Aline Picard; Guillaume Legendre; Elise Riquin (BMC, 2022)
Plain English Summary Eating disorders are frequent pathologies that primarily affect women of childbearing age. Numerous articles reveal an increased risk for the mother and the child in case of an active disorder during pregnancy. We conducted a systematic review to determine the prevalence and phenotypes of eating disorders in infertile subjects undergoing fertility treatment. The results of the fifteen articles included show a prevalence six times higher than in pregnant women in the general population. Subjects with eating disorders have normal body mass indexes. The active forms are mainly characterized by episodes of binge eating disorders or other unspecified forms. Studies also describe incomplete forms characterized by the presence of dysfunctional thoughts around shape and weight without associated compensatory behavior. Professionals working in the field of reproductive medicine and providing fertility treatment have a major role to play in identifying and referring these subjects at risk to specialized care.